Preventive measures of respiratory diseases and impact on employee morbidity - possibilities of using electronic platforms - Václavíková, Klára; Šoukalová, Kristýna; Kožená, Marcela; Brodský, Zdeněk; Mandysová, Michaela; Ochtinská, Hana; Šatera, Karel; Horáčková, Kateřina (Vojenské zdravotnické listy, 2024)
Aims: Prevention is one of the most effective methods in the fight against respiratory infections. Electronic platforms can streamline care and have positive applications in the case of infectious diseases. This study was conducted to search for and describe the current scientific knowledge on prevention and the use of electronic platforms and their impact on the application of prevention strategies.Methods: A scoping review was conducted. In January 2022, a search was performed in selected licensed and free databases (EBSCOhost, Ovid, Scopus, Web of Science) based on PCC keywords using Boolean operators.Results: A total of 1927 sources were retrieved, of which 21 were subjected to critical analysis. 8 sources were included in the final review. Vaccination, social isolation, hygienic hand disinfection and respiratory protection are described as the most common and effective preventive measures. The platforms described had a positive effect on prevention and improving the quality of care.Conclusion: The effectiveness of the use of electronic platforms in prevention has been confirmed. Future research should be directed towards the development of these platforms to enable better diagnosis and treatment. Prevention-focused platforms can facilitate, simplify and improve care and access in the prevention of respiratory diseases.
Keywords: Respiratory Tract Diseases; morbidita; Workforce; Primary Prevention; nemoci dýchací soustavy; Humans; pracovní síly; primární prevence; Morbidity; klinická studie jako téma; lidé; Clinical Studies as Topic